Quantitative skin prick and bronchial provocation tests with platinum salt. Issue 12 (December 1991) - Merget, R; Schultze-Werninghaus, G; Bode, F; Bergmann, E M; Zachgo, W; Meier-Sydow, J
Abstract : Occupational asthma due to platinum salts is a frequent disease in platinum refineries. The diagnosis is based upon a history of work related symptoms and a positive skin prick test with platinum salts. Bronchial provocation tests have not been performed in epidemiological studies because the skin test is believed to be highly specific and sensitive. As no reliable data about this issue currently exist, this study assesses the use of skin prick and bronchial provocation tests with methacholine and platinum salt in platinum refinery workers. Twenty seven of 35 workers, who were referred to our clinic with work related symptoms and nine control subjects with bronchial hyperreactivity underwent a skin prick test and bronchial provocation with methacholine and platinum salt. For skin prick and bronchial provocation tests with platinum salt a 10(-2)-10(-8) mol/l hexachloroplatinic acid solution, in 10-fold dilutions was used. Four of the 27 subjects and all controls showed neither a bronchial reaction nor a skin reaction. Twenty three subjects were considered allergic to platinum salt; 22 of these showed a fall of 50% or more in specific airway conductance after inhalation of the platinum salt solution. Four workers experienced a positive bronchial reaction despite a negative skin prick test. No correlation of responsiveness to methacholine with responsiveness to platinum salt was found, but the skin prick test correlated with the bronchial reaction to platinum salt (rs = 0.50, p less than 0.023, n = 22). One dual reaction was seen in bronchial provocation tests. Side effects of both skin tests and bronchial provocation tests with platinum salt were rare and were not encountered in workers without a skin reaction to platinum salt. It is concluded that bronchial provocation tests with platinum salts should be performed on workers with work related symptoms but negative skin tests with platinum salts.